Hypoxia within subcutaneously implanted macroencapsulation devices limits the viability and functionality of densely loaded islets - Einstein, Samuel A.; Steyn, Leah V.; Weegman, Bradley P.; Suszynski, Thomas M.; Sambanis, Athanassios; O’Brien, Timothy D.; Avgoustiniatos, Efstathios S.; Firpo, Meri T.; Graham, Melanie L.; Janecek, Jody; Eberly, Lynn E.; Garwood, Michael; et al. (Frontiers in Transplantation, 2023)
Introduction: Subcutaneous macroencapsulation devices circumvent disadvantages of intraportal islet therapy. However, a curative dose of islets within reasonably sized devices requires dense cell packing. We measured internal PO2 of implanted devices, mathematically modeled oxygen availability within devices and tested the predictions with implanted devices containing densely packed human islets. Methods: Partial pressure of oxygen (PO2) within implanted empty devices was measured by noninvasive 19 F-MRS. A mathematical model was constructed, predicting internal PO2, viability and functionality of densely packed islets as a function of external PO2. Finally, viability was measured by oxygen consumption rate (OCR) in day 7 explants loaded at various islet densities. Results: In empty devices, PO2 was 12 mmHg or lower, despite successful external vascularization. Devices loaded with human islets implanted for 7 days, then explanted and assessed by OCR confirmed trends proffered by the model but viability was substantially lower than predicted. Co-localization of insulin and caspase-3 immunostaining suggested that apoptosis contributed to loss of beta cells. Discussion: Measured PO2 within empty devices declined during the first few days post-transplant then modestly increased with neovascularization around the device. Viability of islets is inversely related to islet density within devices.